Orthopedic applications of 3D printing in canine veterinary medicine - Thomas, Claire; Amsellem, Pierre; Nascene, David; Huang, Yu-Hui (Frontiers in Veterinary Science, 2025)
ObjectiveThis case series investigates the application of 3D printing in veterinary orthopedic surgeries, emphasizing its potential to enhance preoperative planning, intraoperative precision, and postoperative outcomes.AnimalsThree canines—German Shepherd, Basset Hound, and Labrador Retriever—were included in this study.Materials and methodsThree canine cases involving complex orthopedic deformities were selected to illustrate different uses of 3D printing in veterinary surgery. CT scans were segmented using Materialise Mimics 26.0, followed by virtual surgical planning and creation of 3D printed models and guides.ResultsIn Case 1, a 2-year-old German Shepherd with a congenital right tibial deformity underwent successful surgical correction aided by a preoperatively prepared external fixator frame, saving approximately 1 h of OR time. In Case 2, a 1-year-old Basset Hound with a left antebrachial deformity had a double wedge osteotomy performed with the assistance of patient-specific cutting and reconstruction guides, leading to optimal alignment and reduced surgical time. Case 3 involved a young, less than 1-year-old Labrador Retriever rescue with severe bilateral tibiofemoral deformity, where 3D printed models helped the surgeon determine that surgery was not the best option, potentially preventing a poor outcome.Clinical relevanceThis case series highlights the transformative potential of 3D printing in veterinary orthopedic surgery, illustrating its ability to improve aid surgical outcomes, reduce operative times, and be a valuable tool in preoperative decision-making. This technology allows for tailored surgical interventions, enhancing the precision and effectiveness of treatment plans in veterinary medicine.